Pituitary volume in adolescents with non-suicidal self-injury: preliminary evidence for alterations in pituitary maturation - Schär, Selina; Mürner-Lavanchy, Ines M.; Slavova, Nedelina; Lerch, Stefan; Reichl, Corinna; Brunner, Romuald; Koenig, Julian; Kaess, Michael (Psychoneuroendocrinology, 2022)
Background - Non-suicidal self-injury (NSSI), typically observed in the context of various mental disorders, represents a highly prevalent and serious problem among adolescents. Based on studies linking NSSI with stress, alterations in hypothalamic-pituitary-adrenal (HPA) axis functioning have been suggested to contribute to the development and maintenance of this behavior. While research has mainly focused on cortisol - the main hormonal output of this system - to our knowledge, no study has examined pituitary gland volume (PGV) - an alternative approach of assessing HPA axis functionality that is less state-dependent - in adolescents engaging in NSSI. - Methods - Magnetic Resonance Imaging (MRI) was performed among n = 35 adolescents (aged 12-17 years) fulfilling the diagnostic criteria for NSSI disorder according to DSM-5 and n = 31 age-matched healthy controls; PGV was obtained by manual tracing. To test for group differences - our primary aim - a hierarchical linear regression model was computed, controlling for several potential confounding variables. Since adolescence reflects a time period for significant brain development - including changes in PGV - we also tested for an age-dependent group effect. In a second step, we aimed to investigate whether differences in PGV are accounted for by the experience of childhood adversity or psychopathology. Finally, following an exploratory approach, the dimensional association between PGV and various clinical characteristics (e.g., frequency of NSSI) were explored. - Results - No evidence was found for overall volumetric differences between healthy control participants and adolescents engaging in NSSI (p > 0.05) - recognizing that small effect size differences could not be detected in the present study - but group membership significantly interacted with age in predicting PGV (p = 0.02). Particularly, while PGV increased linearly with age in healthy controls (B = 61.39, SE = 14.94, p < 0.01), no corresponding association was found in NSSI patients (B = 16.83, SE = 12.20, p = 0.17). PGV was not related to adverse experiences during childhood and none of the clinical characteristics (e.g., frequency of NSSI) significantly correlated with PGV (p > 0.05). - Conclusion - These results provide preliminary evidence for alterations in pituitary maturation in adolescents engaging in NSSI, although replication in longitudinal studies with larger samples is warranted.